Intimate partner violence in pregnancy: a cross-sectional study from post-conflict northern Uganda. Issue 11 (26th November 2019) - Clarke, Susan; Richmond, Robyn; Black, Eleanor; Fry, Helen; Obol, James Henry; Worth, Heather
Abstract : Objectives: To determine the prevalence of intimate partner violence (IPV) in pregnancy and to understand associations and determinants. Design: Cross-sectional survey. Setting: Two rural health clinics in post-conflict northern Uganda. Participants: Women attending two rural health clinics for a new service providing cervical cancer screening, who had experienced pregnancy. Primary and secondary outcome measures: Data were collected by a questionnaire using validated questions from the demographic health survey women's questionnaire and the domestic violence module. Data were entered into tablets using Questionnaire Development System software. Bivariate and multivariate logistic regression was performed, using experience of IPV in pregnancy as the dependent variable. SPSS V.25 was used for all analysis. Results: Of 409 participant women, 26.7% (95% CI 18.6% to 35.9%) reported having been slapped, hit or beaten by a partner while pregnant. For 32.3% (95% CI 20.2% to 37.9%) of the women the violence became worse during pregnancy. Women who had ever experienced IPV in pregnancy were more likely to have experienced violence in the previous 12 months (OR 4.45, 95% CI 2.80 to 7.09). In multivariate logistic regression, the strongest independent associations with IPV in pregnancy were partner's daily drinking of alcohol (OR 2.02, 95% CI 1.19 to 3.43) and controlling behaviours (OR 1.17, 95% CI 1.03 to 1.33). Conclusions: The women in this study had more exposure to IPV in pregnancy than previously reported for this region. Women's previous experience of intimate partner violence, partner's daily use of alcohol and his controlling behaviours were strong associations with IPV in pregnancy. This study highlights the uneven distribution of risk and the importance of research among the most vulnerable population in rural and disadvantaged settings. More research is needed in local rural and urban settings to illuminate this result and inform intervention and policy.